Insulin receptor in the brain: Mechanisms of activation and the role in the CNS pathology and treatment. (24th April 2018) - Pomytkin, Igor; Costa‐Nunes, João P.; Kasatkin, Vladimir; Veniaminova, Ekaterina; Demchenko, Anna; Lyundup, Alexey; Lesch, Klaus‐Peter; Ponomarev, Eugene D.; Strekalova, Tatyana
Summary: While the insulin receptor (IR) was found in the CNS decades ago, the brain was long considered to be an insulin‐insensitive organ. This view is currently revisited, given emerging evidence of critical roles of IR‐mediated signaling in development, neuroprotection, metabolism, and plasticity in the brain. These diverse cellular and physiological IR activities are distinct from metabolic IR functions in peripheral tissues, thus highlighting region specificity of IR properties. This particularly concerns the fact that two IR isoforms, A and B, are predominantly expressed in either the brain or peripheral tissues, respectively, and neurons express exclusively IR‐A. Intriguingly, in comparison with IR‐B, IR‐A displays high binding affinity and is also activated by low concentrations of insulin‐like growth factor‐2 (IGF‐2), a regulator of neuronal plasticity, whose dysregulation is associated with neuropathologic processes. Deficiencies in IR activation, insulin availability, and downstream IR‐related mechanisms may result in aberrant IR‐mediated functions and, subsequently, a broad range of brain disorders, including neurodevelopmental syndromes, neoplasms, neurodegenerative conditions, and depression. Here, we discuss findings on the brain‐specific features of IR‐mediated signaling with focus on mechanisms of primary receptor activation and their roles in the neuropathology. We aimed to uncover the remaining gaps in current knowledge on IR physiology and highlight new therapies targeting IR, such as IR sensitizers.